2011
DOI: 10.1002/med.20248
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the multitarget‐directed ligands approach for the treatment of Alzheimer's disease

Abstract: With 27 million cases worldwide documented in 2006, Alzheimer's disease (AD) constitutes an overwhelming health, social, economic, and political problem to nations. Unless a new medicine capable to delay disease progression is found, the number of cases will reach 107 million in 2050. So far, the therapeutic paradigm one‐compound‐one‐target has failed. This could be due to the multiple pathogenic mechanisms involved in AD including amyloid β (Aβ) aggregation to form plaques, τ hyperphosphorylation to disrupt m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
264
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 409 publications
(268 citation statements)
references
References 345 publications
2
264
0
2
Order By: Relevance
“…In addition to specific protein targets, developed hybrid molecules can also incorporate antioxidant or anti-amyloid fragments [18]. Several review articles describing the status and advances of this class of MTDLs have been recently published, to whom the reader is directed for a more comprehensive discussion [19][20][21][22][23][24].…”
Section: Development Of Memantine-galantamine Hybrids Via a Linking Smentioning
confidence: 99%
“…In addition to specific protein targets, developed hybrid molecules can also incorporate antioxidant or anti-amyloid fragments [18]. Several review articles describing the status and advances of this class of MTDLs have been recently published, to whom the reader is directed for a more comprehensive discussion [19][20][21][22][23][24].…”
Section: Development Of Memantine-galantamine Hybrids Via a Linking Smentioning
confidence: 99%
“…quinolizidine and lycopodium alkaloids such as huperzine, which promotes competitive inhibition; isoquinolines such as aporphyrin and benzylisoquinoline, which are non-competitive compounds, and galantamine and lycorine, which are competitive; and indole alkaloids, which are divided into indole alkaloids, monoterpenes and physostigmine, which are competitive, and quaternary beta-carbolines, which are non-competitive. 18,19,25 Out of all of these, we highlight huperzine as a potent, selective and reversible inhibitor of AChE. This is used in cases of myasthenia gravis, organophosphate poisoning and schizophrenia.…”
Section: Phospholipase A2 Inhibitorsmentioning
confidence: 99%
“…Furthermore, it needs to be borne in mind that statins have a risky safety profile and there may be hepatic impairment and risk of rhabdomyolysis at doses that would be effective for continuous treatment of AD. 18,20 In a meta-analysis on separately evaluated cross-sectional and longitudinal observational studies (total of 19), the crosssectional studies showed that statins had a protective effect, and it was noted that use of statins was associated with a reduced risk of developing AD and other forms of dementia. However, progress in such studies is still restricted by bias in some of them.…”
Section: Tamibarotenementioning
confidence: 99%
See 2 more Smart Citations